g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
foldB(t, 0) → t
foldB(t, s(n)) → f(foldB(t, n), B)
foldC(t, 0) → t
foldC(t, s(n)) → f(foldC(t, n), C)
f(t, x) → f'(t, g(x))
f'(triple(a, b, c), C) → triple(a, b, s(c))
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f'(triple(a, b, c), A) → f''(foldB(triple(s(a), 0, c), b))
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
fold(t, x, 0) → t
fold(t, x, s(n)) → f(fold(t, x, n), x)
↳ QTRS
↳ DependencyPairsProof
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
foldB(t, 0) → t
foldB(t, s(n)) → f(foldB(t, n), B)
foldC(t, 0) → t
foldC(t, s(n)) → f(foldC(t, n), C)
f(t, x) → f'(t, g(x))
f'(triple(a, b, c), C) → triple(a, b, s(c))
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f'(triple(a, b, c), A) → f''(foldB(triple(s(a), 0, c), b))
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
fold(t, x, 0) → t
fold(t, x, s(n)) → f(fold(t, x, n), x)
F'(triple(a, b, c), A) → FOLDB(triple(s(a), 0, c), b)
FOLDC(t, s(n)) → FOLDC(t, n)
F(t, x) → G(x)
FOLDB(t, s(n)) → F(foldB(t, n), B)
FOLD(t, x, s(n)) → F(fold(t, x, n), x)
FOLDC(t, s(n)) → F(foldC(t, n), C)
F'(triple(a, b, c), B) → F(triple(a, b, c), A)
F(t, x) → F'(t, g(x))
F'(triple(a, b, c), A) → F''(foldB(triple(s(a), 0, c), b))
FOLDB(t, s(n)) → FOLDB(t, n)
FOLD(t, x, s(n)) → FOLD(t, x, n)
F''(triple(a, b, c)) → FOLDC(triple(a, b, 0), c)
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
foldB(t, 0) → t
foldB(t, s(n)) → f(foldB(t, n), B)
foldC(t, 0) → t
foldC(t, s(n)) → f(foldC(t, n), C)
f(t, x) → f'(t, g(x))
f'(triple(a, b, c), C) → triple(a, b, s(c))
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f'(triple(a, b, c), A) → f''(foldB(triple(s(a), 0, c), b))
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
fold(t, x, 0) → t
fold(t, x, s(n)) → f(fold(t, x, n), x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
F'(triple(a, b, c), A) → FOLDB(triple(s(a), 0, c), b)
FOLDC(t, s(n)) → FOLDC(t, n)
F(t, x) → G(x)
FOLDB(t, s(n)) → F(foldB(t, n), B)
FOLD(t, x, s(n)) → F(fold(t, x, n), x)
FOLDC(t, s(n)) → F(foldC(t, n), C)
F'(triple(a, b, c), B) → F(triple(a, b, c), A)
F(t, x) → F'(t, g(x))
F'(triple(a, b, c), A) → F''(foldB(triple(s(a), 0, c), b))
FOLDB(t, s(n)) → FOLDB(t, n)
FOLD(t, x, s(n)) → FOLD(t, x, n)
F''(triple(a, b, c)) → FOLDC(triple(a, b, 0), c)
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
foldB(t, 0) → t
foldB(t, s(n)) → f(foldB(t, n), B)
foldC(t, 0) → t
foldC(t, s(n)) → f(foldC(t, n), C)
f(t, x) → f'(t, g(x))
f'(triple(a, b, c), C) → triple(a, b, s(c))
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f'(triple(a, b, c), A) → f''(foldB(triple(s(a), 0, c), b))
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
fold(t, x, 0) → t
fold(t, x, s(n)) → f(fold(t, x, n), x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ UsableRulesProof
↳ QDP
F'(triple(a, b, c), A) → FOLDB(triple(s(a), 0, c), b)
FOLDC(t, s(n)) → FOLDC(t, n)
FOLDB(t, s(n)) → F(foldB(t, n), B)
FOLDC(t, s(n)) → F(foldC(t, n), C)
F'(triple(a, b, c), B) → F(triple(a, b, c), A)
F(t, x) → F'(t, g(x))
F'(triple(a, b, c), A) → F''(foldB(triple(s(a), 0, c), b))
FOLDB(t, s(n)) → FOLDB(t, n)
F''(triple(a, b, c)) → FOLDC(triple(a, b, 0), c)
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
foldB(t, 0) → t
foldB(t, s(n)) → f(foldB(t, n), B)
foldC(t, 0) → t
foldC(t, s(n)) → f(foldC(t, n), C)
f(t, x) → f'(t, g(x))
f'(triple(a, b, c), C) → triple(a, b, s(c))
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f'(triple(a, b, c), A) → f''(foldB(triple(s(a), 0, c), b))
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
fold(t, x, 0) → t
fold(t, x, s(n)) → f(fold(t, x, n), x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
FOLDC(t, s(n)) → FOLDC(t, n)
F'(triple(a, b, c), A) → FOLDB(triple(s(a), 0, c), b)
FOLDB(t, s(n)) → F(foldB(t, n), B)
FOLDC(t, s(n)) → F(foldC(t, n), C)
F(t, x) → F'(t, g(x))
F'(triple(a, b, c), B) → F(triple(a, b, c), A)
F'(triple(a, b, c), A) → F''(foldB(triple(s(a), 0, c), b))
FOLDB(t, s(n)) → FOLDB(t, n)
F''(triple(a, b, c)) → FOLDC(triple(a, b, 0), c)
foldB(t, 0) → t
foldB(t, s(n)) → f(foldB(t, n), B)
f'(triple(a, b, c), A) → f''(foldB(triple(s(a), 0, c), b))
f(t, x) → f'(t, g(x))
foldC(t, s(n)) → f(foldC(t, n), C)
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
foldC(t, 0) → t
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
f'(triple(a, b, c), C) → triple(a, b, s(c))
FOLDC(t, s(n)) → FOLDC(t, n)
F'(triple(a, b, c), A) → FOLDB(triple(s(a), 0, c), b)
FOLDB(t, s(n)) → FOLDB(t, n)
foldB(t, s(n)) → f(foldB(t, n), B)
POL(0) = 0
POL(A) = 1
POL(B) = 1
POL(C) = 1
POL(F(x1, x2)) = x1 + 2·x2
POL(F'(x1, x2)) = x1 + 2·x2
POL(F''(x1)) = 1 + x1
POL(FOLDB(x1, x2)) = x1 + 2·x2
POL(FOLDC(x1, x2)) = 1 + x1 + x2
POL(f(x1, x2)) = x1 + x2
POL(f'(x1, x2)) = x1 + x2
POL(f''(x1)) = x1
POL(foldB(x1, x2)) = x1 + 2·x2
POL(foldC(x1, x2)) = x1 + x2
POL(g(x1)) = x1
POL(s(x1)) = 1 + x1
POL(triple(x1, x2, x3)) = 2 + x1 + 2·x2 + x3
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
FOLDB(t, s(n)) → F(foldB(t, n), B)
FOLDC(t, s(n)) → F(foldC(t, n), C)
F'(triple(a, b, c), B) → F(triple(a, b, c), A)
F(t, x) → F'(t, g(x))
F'(triple(a, b, c), A) → F''(foldB(triple(s(a), 0, c), b))
F''(triple(a, b, c)) → FOLDC(triple(a, b, 0), c)
foldB(t, 0) → t
f'(triple(a, b, c), A) → f''(foldB(triple(s(a), 0, c), b))
f(t, x) → f'(t, g(x))
foldC(t, s(n)) → f(foldC(t, n), C)
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
foldC(t, 0) → t
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
f'(triple(a, b, c), C) → triple(a, b, s(c))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
FOLDC(t, s(n)) → F(foldC(t, n), C)
F'(triple(a, b, c), B) → F(triple(a, b, c), A)
F(t, x) → F'(t, g(x))
F'(triple(a, b, c), A) → F''(foldB(triple(s(a), 0, c), b))
F''(triple(a, b, c)) → FOLDC(triple(a, b, 0), c)
foldB(t, 0) → t
f'(triple(a, b, c), A) → f''(foldB(triple(s(a), 0, c), b))
f(t, x) → f'(t, g(x))
foldC(t, s(n)) → f(foldC(t, n), C)
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
foldC(t, 0) → t
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
f'(triple(a, b, c), C) → triple(a, b, s(c))
F'(triple(a, b, c), A) → F''(foldB(triple(s(a), 0, c), b))
f'(triple(a, b, c), A) → f''(foldB(triple(s(a), 0, c), b))
POL(0) = 0
POL(A) = 2
POL(B) = 2
POL(C) = 2
POL(F(x1, x2)) = x1 + x2
POL(F'(x1, x2)) = x1 + x2
POL(F''(x1)) = x1
POL(FOLDC(x1, x2)) = x1 + 2·x2
POL(f(x1, x2)) = x1 + x2
POL(f'(x1, x2)) = x1 + x2
POL(f''(x1)) = x1
POL(foldB(x1, x2)) = x1 + x2
POL(foldC(x1, x2)) = x1 + 2·x2
POL(g(x1)) = x1
POL(s(x1)) = 1 + x1
POL(triple(x1, x2, x3)) = x1 + 2·x2 + 2·x3
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
FOLDC(t, s(n)) → F(foldC(t, n), C)
F(t, x) → F'(t, g(x))
F'(triple(a, b, c), B) → F(triple(a, b, c), A)
F''(triple(a, b, c)) → FOLDC(triple(a, b, 0), c)
foldB(t, 0) → t
f(t, x) → f'(t, g(x))
foldC(t, s(n)) → f(foldC(t, n), C)
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
foldC(t, 0) → t
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
f'(triple(a, b, c), C) → triple(a, b, s(c))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
F'(triple(a, b, c), B) → F(triple(a, b, c), A)
F(t, x) → F'(t, g(x))
foldB(t, 0) → t
f(t, x) → f'(t, g(x))
foldC(t, s(n)) → f(foldC(t, n), C)
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
foldC(t, 0) → t
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
f'(triple(a, b, c), C) → triple(a, b, s(c))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
F(t, x) → F'(t, g(x))
F'(triple(a, b, c), B) → F(triple(a, b, c), A)
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
F(t, x) → F'(t, g(x))
F'(triple(a, b, c), B) → F(triple(a, b, c), A)
g(B) → A
g(C) → A
POL(A) = 0
POL(B) = 2
POL(C) = 2
POL(F(x1, x2)) = 1 + 2·x1 + 2·x2
POL(F'(x1, x2)) = 2·x1 + 2·x2
POL(g(x1)) = x1
POL(triple(x1, x2, x3)) = 2 + x1 + 2·x2 + x3
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ RuleRemovalProof
↳ QDP
↳ PisEmptyProof
↳ QDP
g(A) → A
g(B) → B
g(C) → B
g(C) → C
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ UsableRulesProof
FOLD(t, x, s(n)) → FOLD(t, x, n)
g(A) → A
g(B) → A
g(B) → B
g(C) → A
g(C) → B
g(C) → C
foldB(t, 0) → t
foldB(t, s(n)) → f(foldB(t, n), B)
foldC(t, 0) → t
foldC(t, s(n)) → f(foldC(t, n), C)
f(t, x) → f'(t, g(x))
f'(triple(a, b, c), C) → triple(a, b, s(c))
f'(triple(a, b, c), B) → f(triple(a, b, c), A)
f'(triple(a, b, c), A) → f''(foldB(triple(s(a), 0, c), b))
f''(triple(a, b, c)) → foldC(triple(a, b, 0), c)
fold(t, x, 0) → t
fold(t, x, s(n)) → f(fold(t, x, n), x)
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ UsableRulesProof
↳ QDP
↳ QDPSizeChangeProof
FOLD(t, x, s(n)) → FOLD(t, x, n)
From the DPs we obtained the following set of size-change graphs: